Ground Flora and their Distribution in Forest Plantations in Jamuna Ravine - Sajwan, S. S. (Indian Forester, 1975)
This paper presents results of a survey of ground flora in forest plantations of Jamuna Ravine conducted at the Soil Conservation Research, Demonstration and Training Centre, Agra (Chhalesar). The study reveals minimum number of ground flora in plantations of Prosopis juliflora and Dendrocalamus strictus and the maximum in that of Dalbergia sissoo. There are some species which are specific in each of the five plantations. Apluda aristata has maximum frequency and density in Dalbergia sissoo, Acacia nilotica and mixed plantations. Regeneration of Dalbergia sissoo has been found in all the plantations except in the one of Prosopis juliflora.